Factors Affecting Students’ Nursing Profession Preference During the Pandemic Period - Eylem Paslı Gürdoğan; Berna Aksoy; Ezgi Kınıcı Dirik; Esin Çetinkaya Uslusoy (Mediterranean Nursing and Midwifery, 2023)

(untitled)
Objective:In this study, it was aimed to determine the factors that affect the nursing profession preference of the first-year nursing students during the Coronavirus disease-2019 (COVID-19) pandemic.Method:This cross-sectional and descriptive study was conducted between March-June 2021 with first-year nursing students studying. Student information form, the fear of COVID-19 scale, and vocational choices in entering the nursing scale were used to collect data.Results:75.4% of the students stated that the COVID-19 pandemic did not affect their career choice, 46% reported that they planned to choose the nursing profession before the pandemic, and 52.1% of the students preferred the nursing profession because they liked it. As a result of multiple regression analysis, factors including fear of COVID-19, presence of chronic disease in family members, choosing the profession because they like it, choosing the profession because of its place and importance in society, choosing the profession because it is an ideal profession, choosing the profession under the influence of family/friends, and choosing nursing because it is seen as an indispensable profession during the pandemic were found to have a significant effect on the total scores of the vocational choices in entering nursing scale (p<0.05).Conclusion:Although the pandemic has caused nurses to work under very difficult conditions, it has once again revealed how important the nursing profession is for society. Despite seeing the difficulties experienced in this process and being afraid of COVID-19, the students chose the nursing profession because they loved it and saw it as indispensable.